Ixodid ticks and zoonotic tick-borne pathogens of the Western Balkans - Kapo, Naida; Zuber Bogdanović, Ivana; Gagović, Ema; Žekić, Marina; Veinović, Gorana; Sukara, Ratko; Mihaljica, Darko; Adžić, Bojan; Kadriaj, Përparim; Cvetkovikj, Aleksandar; Dјadјovski, Igor; Potkonjak, Aleksandar; et al. (Springer Science and Business Media LLC, 2024)
Ixodid ticks are distributed across all countries of the Western Balkans, with a high diversity of species. Many of these species serve as vectors of pathogens of veterinary and medical importance. Given the scattered data from Western Balkan countries, we have conducted a comprehensive review of available literature, including some historical data, with the aim to compile information about all recorded tick species and associated zoonotic pathogens in this region. Based on the collected data, the tick fauna of the Western Balkans encompasses 32 tick species belonging to five genera: Ixodes, Haemaphysalis, Dermacentor, Rhipicephalus and Hyalomma. A range of pathogens responsible for human diseases has also been documented, including viruses, bacteria and parasites. In this review, we emphasize the necessity for integrated surveillance and reporting, urging authorities to foster research by providing financial support. Additionally, international and interdisciplinary collaborations should be encouraged that include the exchange of expertise, experiences and resources. The present collaborative effort can effectively address gaps in our knowledge of ticks and tick-borne diseases.